Preparation method of carbon-based material dispersion for coating resistant to high-temperature molten salt corrosion

By crushing, spherical shaping, fusion shaping and wet grinding of carbon-based materials, the problems of high cost and difficult construction of existing coatings are solved, and a low-cost, easy-to-construct carbon-based coating is achieved, with excellent High temperature resistance and good dispersion effect, suitable for high temperature molten salt corrosion environment.

CN119263250APending Publication Date: 2025-01-07BAOWU CHARCOAL MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310779409.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing high-temperature anti-corrosion coatings have high cost, long construction cycle and poor density, making it difficult to effectively reduce the corrosion of molten salt on container materials. Especially at high temperatures, the dispersion effect and particle size distribution of carbon-based materials are not sufficient to exert their high-temperature resistance.

Method used

The small-particle spheroidized carbon-based material dispersion is obtained through a variety of processing steps, including crushing, spheroidization shaping, fusion shaping and wet grinding, ensuring the good dispersion effect and particle size distribution of carbon-based materials in water, reducing the coating Preparation cost and construction difficulty.

Benefits of technology

It realizes a low-cost, easy-to-construct carbon-based coating with excellent high temperature resistance. The coating can be durable for 3000 hours in molten salt at 565°C, and the average annual corrosion rate is less than 10 microns/year.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263250A_ABST
    Figure CN119263250A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a carbon-based material dispersion for a high-temperature molten salt corrosion resistant coating. The preparation method comprises the following steps: S1, obtaining a sphere-like carbon-based material with a D50 particle size of 7-12 microns; and S2, mixing the sphere-like carbon-based material, a solvent and a dispersing agent, and dispersing by wet grinding to obtain the carbon-based material dispersion with the D50 particle size of 0.5-3 microns. According to the preparation method, the carbon-based material is treated in multiple modes, and the small-particle-size spheroidized carbon-based material dispersion is obtained through dispersion with a wet grinding method; by treating the carbon-based material, the dispersion effect and particle size distribution of the carbon-based material in water are ensured, and the preparation cost and construction difficulty of the high-temperature molten salt corrosion resistant coating can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature anti-corrosion coatings, and in particular relates to a method for preparing a carbon-based material dispersion for a high-temperature molten salt corrosion-resistant coating. Background Art

[0002] Concentrated solar thermal power generation (CSP) has long-term safe heat storage technology. Concentrated solar power generation has the characteristics of low carbon, clean, self-contained energy storage, and strong regulation ability. It can better cope with the challenges faced by high-proportion new energy power systems. It is a flexible clean power source that can play the role of ballast in new power systems. As a new energy and renewable energy development technology with huge development potential, it has attracted much attention. Many countries have invested a lot of money and manpower in research. According to relevant statistical data, the carbon emissions per kilowatt-hour of coal-fired power generation and natural gas combined cycle power generation throughout the life cycle are as high as 746 grams and 532.3 grams respectively, while tower-type concentrated solar power generation is only 15.3 grams. The high-temperature heat storage system in concentrated solar power generation technology is a very critical module. In order to improve the efficiency of power generation, molten salt is often used as a heat transfer and heat storage medium, but molten salt is easy to corrode the container material at high temperatures.

[0003] There are roughly three methods to reduce the corrosion of container materials by molten salts. One is to improve the corrosion resistance of container materials by adding elements such as chromium, molybdenum and nickel to the container materials; the second is to add a small amount of divalent alkaline earth metals as corrosion inhibitors to the molten salt to achieve the effect of reducing corrosion; the third is to deposit a coating on the surface of the container material, which can reduce the corrosion of the container material by blocking the direct interaction between the molten salt and the container material, and on the other hand, it can delay the corrosion of the container material by sacrificing the coating material. The most commonly used coating main components in the field of high temperature corrosion resistance are metals and ceramics. Chinese Patent Publication No. CN115418592A discloses a chloride molten salt corrosion resistant coating and its preparation method. Compared with traditional hot-dip aluminum plating, the patent uses Fe-Cr-B alloy hot-dip Al-Si alloy to obtain a special coating with better chloride molten salt corrosion resistance. Although the metal coating in the above technology has excellent adhesion, high temperature resistance and high temperature molten salt corrosion resistance, it has defects such as high cost, long construction period and poor coating density. Compared with alloy material improvement and molten salt modification, the effect of depositing coating on the surface of container material is good. In recent years, coatings with carbon-based materials as the main component have attracted more and more attention from academia and industry due to their excellent high temperature resistance and low cost. Therefore, it is very necessary to develop a low-cost, easy-to-construct carbon-based coating resistant to high temperature molten salt corrosion. The preparation of carbon-based materials is the premise and core of carbon-based coatings resistant to high temperature molten salt corrosion, especially the dispersion effect and particle size distribution of carbon-based materials, which are the key to whether carbon-based materials can play their role. In view of this, it is urgent to develop a method for preparing a carbon-based material dispersion for carbon-based coatings resistant to high temperature molten salt corrosion, so that the carbon-based material dispersion has a suitable particle size distribution and a stable dispersion effect of particles. Summary of the invention

[0004] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a method for preparing a carbon-based material dispersion for a high-temperature molten salt corrosion resistant coating, wherein the carbon-based material is treated in a variety of ways, and a small-particle spheroidized carbon-based material dispersion is obtained by wet grinding. By treating the carbon-based material, the present invention enables the carbon-based material to have a good dispersion effect and particle size distribution in water, thereby effectively reducing the preparation cost and construction difficulty of the high-temperature molten salt corrosion resistant coating.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] The present invention provides a method for preparing a carbon-based material dispersion for a high-temperature molten salt corrosion-resistant coating, comprising the following steps:

[0007] S1, obtaining a spherical carbon-based material with a D50 particle size of 7 to 12 microns;

[0008] S2, mixing the spherical carbon-based material, a solvent and a dispersant, and dispersing the mixture by wet grinding to obtain a carbon-based material dispersion with a particle size of 0.5 to 3 micrometers.

[0009] Preferably, step S1 comprises the following steps:

[0010] S11, crushing the carbon-based material to obtain micron-sized carbon-based material powder with uniform particle size distribution;

[0011] S12, performing spheroidization and shaping treatment on the micron-sized carbon-based material powder after the pulverization treatment to remove fine particles in the powder to obtain a spheroidized carbon-based material;

[0012] S13, subjecting the spheroidized carbon-based material to fusion shaping treatment to modify the edges and corners of the particles to obtain a spherical carbon-based material.

[0013] Preferably, in step S11, the particle size of the carbon-based material is less than 2 mm.

[0014] Preferably, in step S11, the particle size distribution of the micron-sized carbon-based material powder is as follows: D10 particle size is 3 to 6 microns, D50 particle size is 7 to 11 microns, and D90 particle size is 15 to 25 microns.

[0015] Preferably, in the step S11, the coarse crusher used in the pulverizing process is a mechanical mill or a roller mill.

[0016] Preferably, in step S12, the particle size distribution of the spheroidized carbon-based material is: D10 particle size is 3.5 to 7 microns, D50 particle size is 7.5 to 12 microns, and D90 particle size is 16 to 30 microns; and / or

[0017] The tap density of the spheroidized carbon-based material is ≥0.7 g·cm 3 .

[0018] Preferably, in step S12, the spheroidizing and shaping machine used in the spheroidizing and shaping treatment is selected from an impact spheroidizing and shaping mill, a batch shaping machine, an airflow vortex mill or an airflow classifier.

[0019] Preferably, in step S13, the particle size distribution of the spherical carbon-based material is as follows: D10 particle size is 3 to 7 microns, D50 particle size is 7 to 12 microns, and D90 particle size is 15 to 30 microns.

[0020] Preferably, in step S13, the fusion shaping process uses a fusion machine.

[0021] Preferably, in step S1, the carbon-based material is one or more of natural graphite, artificial graphite precursor, artificial graphite and negative electrode dust removal powder.

[0022] Preferably, the specific process of step S2 is as follows:

[0023] A wet grinder is used for wet grinding, and zirconium beads with a diameter of 0.4 to 3 mm are used as wet grinding media. The spherical carbon-based material, solvent and dispersant are added into the barrel of the wet grinder, and low-speed pre-stirring is first performed to fully mix the spherical carbon-based material, solvent and dispersant. The grinder is then operated at a speed of 1000 to 4000 r / min, and samples are taken every 2 hours for particle size testing. After the particle size meets the requirements, the zirconium beads are separated to obtain a carbon-based material dispersion with a D50 particle size of 0.5 to 3 microns.

[0024] Preferably, in step S2, the stirring rate of the low-speed pre-stirring is 300-600 r / min.

[0025] Preferably, in step S2, the particle size detection adopts laser particle size testing.

[0026] Preferably, in step S2:

[0027] The solid-to-liquid ratio of the mixture of the spherical carbon-based material, the solvent and the dispersant is 1:2 to 1:4; and / or

[0028] The proportion of the dispersant in the mixture of the spherical carbon-based material, the solvent and the dispersant is 1 to 10 wt‰; and / or

[0029] The solvent is deionized water; and / or

[0030] The dispersant is selected from one or two of KYC-913, KYC-9366 of Keying Chemical, and BYK-P104 of BYK Chemical.

[0031] Preferably, the particle size distribution of the carbon-based material dispersion is as follows: D10 particle size is 0.1 to 1.5 microns, D50 particle size is 0.5 to 3 microns, and D90 particle size is 1.5 to 6.5 microns.

[0032] The method for preparing a carbon-based material dispersion for a high-temperature molten salt corrosion-resistant coating provided by the present invention has the following beneficial effects:

[0033] 1. The carbon-based materials in the present invention have a wide range of sources and a large output. Different raw material sources can be used based on different requirements and the process can be simplified, making it easy for industrial production;

[0034] 2. The present invention adopts wet grinding of carbon-based materials to obtain a carbon-based material dispersion with nanoparticles and a narrow particle size distribution, and the coating can be directly prepared later;

[0035] 3. The carbon-based material in the carbon-based material dispersion prepared by the present invention has a small particle size and is evenly dispersed. The coating as the main component has excellent high temperature resistance and low cost;

[0036] 4. The present invention uses a variety of methods to treat the carbon-based material, and disperses it by wet grinding to obtain a small-particle spheroidized carbon-based material dispersion; the present invention ensures the dispersion effect and particle size distribution of the carbon-based material in water by treating the carbon-based material, which can effectively reduce the preparation cost and construction difficulty of the high-temperature molten salt corrosion-resistant coating;

[0037] 5. The present invention aims to solve the corrosion problem of metal materials in high-temperature molten salts by processing carbon-based materials to ensure the particle size and dispersion effect of the carbon-based materials. After the coating prepared by the carbon-based material dispersion is coated on the surface of the metal substrate, the average annual corrosion rate is less than 10 microns / year after being immersed in molten salt at 565°C for 3000 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0039] Figure 1 The SEM images of the needle coke after treatment in Example 1 of the present invention are shown in FIG. 1 , wherein (a) is a SEM image of the needle coke after crushing; (b) is a SEM image of the needle coke after spheroidization and shaping; (c) is a SEM image of the needle coke after fusion and shaping;

[0040] Figure 2 The SEM images of the treated green needle coke in Example 2 of the present invention are shown in FIG. 1 , wherein (a) is a SEM image of the green needle coke after crushing; (b) is a SEM image of the green needle coke after spheroidization and shaping; (c) is a SEM image of the green needle coke after fusion and shaping;

[0041] Figure 3 This is a SEM image of a single particle of artificial graphite in Example 3 of the present invention. DETAILED DESCRIPTION

[0042] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.

[0043] Combination Figure 1 As shown, a method for preparing a carbon-based material dispersion for a high-temperature molten salt corrosion-resistant coating comprises the following steps:

[0044] S1, obtaining a spherical carbon-based material with a D50 particle size of 7 to 12 microns; specifically comprising the following steps:

[0045] S11, crushing the carbon-based material to obtain micron-sized carbon-based material powder with uniform particle size distribution;

[0046] Specifically, a certain mass of carbon-based material is subjected to a crushing treatment such as a roller mill through a coarse crusher to obtain a micron-sized carbon-based material powder with uniform particle size distribution. The coarse crusher used for the crushing treatment is a mechanical mill or a roller mill. The particle size distribution of the processed micron-sized carbon-based material powder is: D10 particle size is 3 to 6 microns, D50 particle size is 7 to 11 microns, and D90 particle size is 15 to 25 microns.

[0047] The carbon-based material may be one or more of natural graphite, artificial graphite precursor, artificial graphite and negative electrode dust removal powder, etc., with a particle size of less than 2 mm. If the carbon-based material is artificial graphite and negative electrode dust removal powder, and its particle size meets the requirements of spherical carbon-based materials, it can directly enter step S2 for wet grinding.

[0048] S12, performing spheroidization and shaping treatment on the micron-sized carbon-based material powder after the pulverization treatment to remove fine particles in the powder to obtain a spheroidized carbon-based material;

[0049] Specifically, the micron-sized carbon-based material powder after pulverization is spheroidized to remove fine particles in the powder and make the particle size distribution more concentrated. The spheroidization treatment makes the carbon-based material as isotropic as possible, which can increase the open porosity of the carbon-based material particles, reduce the closed porosity, and effectively increase the tap density. Among them, the tap density of the spheroidized carbon-based material is ≥0.7g·cm 3 .

[0050] The particle size distribution of the spheroidized carbon-based material obtained after treatment is: D10 particle size is 3.5-7 microns, D50 particle size is 7.5-12 microns, and D90 particle size is 16-30 microns. According to the specific product development requirements, 2-3 repeated spheroidization shaping treatments can be performed to obtain spheroidized carbon-based materials with narrow target particle size distribution.

[0051] The spheroidizing and shaping machine used in the spheroidizing and shaping treatment is selected from an impact spheroidizing and shaping mill, a batch shaping machine, an air flow vortex mill or an air flow classifier.

[0052] S13, performing fusion shaping treatment on the spheroidized carbon-based material after the spheroidization shaping treatment to modify the edges and corners of the particles to obtain a spherical carbon-based material.

[0053] Specifically, the spheroidized carbon-based material after spheroidization shaping is fused and shaped by a fusion machine. During the fusion and extrusion process of the fusion machine, the edges and corners of the particles are modified to obtain a spherical carbon-based material with a particle distribution of: D10 particle size is 3 to 7 microns, D50 particle size is 7 to 12 microns, and D90 particle size is 15 to 30 microns. The fusion machine is a high-efficiency fusion machine.

[0054] S2, mixing the spherical carbon-based material, the solvent and the dispersant, and dispersing them by wet grinding to obtain a carbon-based material dispersion with a D50 particle size of 0.5 to 3 microns.

[0055] The specific process is as follows: the spherical carbon-based material is wet-grinded and dispersed, specifically using a wet grinder for wet grinding, using 0.4-3mm zirconium beads as wet grinding media, adding the spherical carbon-based material, solvent and dispersant into the barrel of the wet grinder, first pre-stirring at a low speed (stirring rate is 300-600r / min) to fully mix the spherical carbon-based material, solvent and dispersant, and then running at a speed of 1000-4000r / min, sampling every 2 hours, and performing a particle size test (specifically using a laser particle size test) until the particle size meets the requirements of the carbon-based material dispersion, then turning off the instrument and separating the zirconium beads from the slurry to obtain a carbon-based material dispersion with a D50 particle size of 0.5-3 microns. In the above process, wet grinding can effectively reduce the particle size of the carbon-based material particles, while narrowing the particle size distribution, and effectively improving the density of the particles. The solvent is deionized water; the dispersant is selected from one or two of KYC-913, KYC-9366 of Keying Chemical, and BYK-P104 of BYK Chemical; the proportion of the dispersant in the mixture of the spherical carbon-based material, the solvent and the dispersant is 1 to 10 wt‰; and the solid-liquid ratio of the mixture of the spherical carbon-based material, the solvent and the dispersant is 1:2 to 1:4.

[0056] The particle size distribution of the carbon-based material dispersion prepared above is as follows: D10 particle size is 0.1-1.5 microns, D50 particle size is 0.5-3 microns, and D90 particle size is 1.5-6.5 microns.

[0057] In the method for preparing the carbon-based material dispersion for the high-temperature molten salt corrosion-resistant coating of the present invention, the dispersion effect and particle size distribution of the particles are crucial, so ensuring the particle size of the carbon-based material and the dispersion of the particles is the key to the present invention.

[0058] The preparation method of the carbon-based material dispersion for the high temperature molten salt corrosion resistant coating of the present invention is further introduced below with reference to specific examples.

[0059] Example 1

[0060] The carbon-based material used in this embodiment is needle coke (artificial graphite precursor); the preparation method of the carbon-based material dispersion for the high temperature molten salt corrosion resistant coating of this embodiment is as follows:

[0061] 100 kg of needle coke cooked coke was subjected to roller milling and grinding (crushing) to obtain micron-grade needle coke powder with uniform particle size distribution, and its particle size distribution was: D10 was 3.18 microns, D50 was 7.91 microns, and D90 was 15.99 microns. The micron-grade carbon-based material powder was subjected to spheroidization and shaping to obtain spheroidized carbon-based material, and its particle size distribution was: D10 was 4.13 microns, D50 was 8.68 microns, and D90 was 16.30 microns. The obtained spheroidized carbon-based material was subjected to fusion shaping to obtain more spherical carbon-based material particles, and its particle size distribution was: D10 was 5.13 microns, D50 was 10.07 microns, and D90 was 18.33 microns, and finally 85 kg of spherical carbon-based material particles were obtained.

[0062] Combination Figure 1 The figures shown from left to right are SEM images of needle coke after crushing, spheroidizing and fusion processing. It can be seen that after the needle coke is respectively processed by crushing, spheroidizing and fusion processing, the particle size distribution is more concentrated and the shape gradually develops into a spherical shape.

[0063] The spherical carbon-based material particles are wet ground and dispersed. 14 kg of spherical carbon-based material, 28 kg of deionized water and 3 kg of dispersant KYC-913 are added to the barrel of the grinder. The grinding medium is 0.4-3 mm zirconium beads. The grinder is then started to fully mix the carbon-based material and deionized water. The grinder is then operated at a speed of 4000 r / min. The slurry is sampled and laser particle size test is performed. After 3 hours, the instrument is turned off, the slurry and the zirconium beads are sieved and separated to obtain a carbon-based material dispersion. The particle size is tested. The results are shown in Table 1. The particle size distribution of the carbon-based material dispersion is: particle size D10 is 0.841 microns, D50 is 1.93 microns, and D90 is 4.32 microns.

[0064] Example 2

[0065] The carbon-based material used in this embodiment is needle coke (artificial graphite precursor); the preparation method of the carbon-based material dispersion for the high temperature molten salt corrosion resistant coating of this embodiment is as follows:

[0066] 100 kg of needle coke green coke was passed through a roller mill to obtain micron-grade needle coke powder with uniform particle size distribution, and its particle size distribution was: D10 was 4.2 microns, D50 was 9.51 microns, and D90 was 18.7 microns. The micron-grade carbon-based material powder was spheroidized to obtain spheroidized carbon-based material, and its particle size distribution was: D10 was 5.8 microns, D50 was 10.50 microns, and D90 was 19.1 microns. The spheroidized carbon-based material micron-grade powder was fused and shaped to obtain more spherical carbon-based material particles, and its particle size distribution was: particle size D10 was 5.6 microns, D50 was 10.32 microns, and D90 was 18.5 microns, and finally 90 kg of spherical carbon-based material particles were obtained.

[0067] Combination Figure 2 The figures shown from left to right are SEM images of needle coke green coke after crushing, spheroidizing and fusion shaping. It can be seen that after the needle coke green coke is respectively subjected to crushing, spheroidizing and fusion shaping, the particle size distribution is more concentrated and the shape gradually develops towards a spherical shape.

[0068] The spherical carbon-based material particles were wet ground and dispersed. 14 kg of carbon-based material, 56 kg of water and 3 kg of dispersant KYC-913 were added to the barrel of the grinder. Zirconium beads of 0.4 to 3 mm were used as grinding media. The grinder was then started and pre-stirred at a low speed to fully mix the carbon-based material and deionized water. The grinder was then operated at a speed of 3600 r / min. The slurry was sampled and laser particle size tested. After 2 hours, the instrument was turned off, the slurry and zirconium beads were sieved and separated to obtain a carbon-based material dispersion. The particle size was tested. The results are shown in Table 1. The particle size distribution is: particle size D10 is 1.12 microns, D50 is 2.93 microns, and D90 is 6.18 microns.

[0069] Example 2

[0070] The carbon-based material used in this embodiment is single-particle artificial graphite (artificial graphite); the preparation method of the carbon-based material dispersion for the high-temperature molten salt corrosion-resistant coating of this embodiment is as follows:

[0071] The single-particle artificial graphite is used as the raw material. The particle size of the single-particle artificial graphite is 10.31 microns. The SEM image of the single-particle artificial graphite is as follows: Figure 3 As shown, the particle size distribution is concentrated and the shape is spherical, which meets the requirements of spherical carbon-based materials, and therefore does not need to undergo the previous crushing treatment, spheroidization shaping treatment and fusion treatment.

[0072] The micron-sized artificial graphite powder was wet-ground and dispersed. 14 kg of single-particle artificial graphite, 28 kg of water and 3 kg of dispersant KYC-913 were added into the barrel. The grinding medium was 0.4-3 mm zirconium beads. The grinder was then started to fully mix the carbon-based material and deionized water. The grinder was then operated at a speed of 4000 r / min. The slurry was sampled and laser particle size tested. After 2 hours, the instrument was turned off and the slurry and zirconium beads were sieved to separate the carbon-based material dispersion. The particle size was tested. The results are shown in Table 1. The particle size distribution was as follows: particle size D10 was 0.149 μm, D50 was 1.25 μm, and D90 was 3.61 μm.

[0073] Table 1 Particle size of carbon-based materials in the examples

[0074]

[0075] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating, characterized in that: The following steps are involved: S1, obtaining a spherical carbon-based material with a D50 particle size of 7 to 12 microns; S2, mixing the spherical carbon-based material, solvent and dispersant, and dispersing the mixture by wet grinding to obtain a carbon-based material dispersion with a particle size of 0.5 to 3 micrometers.

2. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 1, characterized in that: The step S1 comprises the following steps: S11, crushing the carbon-based material to obtain micron-sized carbon-based material powder with uniform particle size distribution; S12, performing spheroidization and shaping treatment on the micron-sized carbon-based material powder after the pulverization treatment to remove fine particles in the powder to obtain a spheroidized carbon-based material; S13, subjecting the spheroidized carbon-based material to fusion shaping treatment to modify the edges and corners of the particles to obtain a spherical carbon-based material.

3. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In the step S11, the particle size of the carbon-based material is less than 2 mm.

4. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In the step S11, the particle size distribution of the micron-sized carbon-based material powder is as follows: D10 particle size is 3 to 6 microns, D50 particle size is 7 to 11 microns, and D90 particle size is 15 to 25 microns.

5. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In the step S11, the coarse crusher used in the pulverizing process is a mechanical mill or a roller mill.

6. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In the step S12: The particle size distribution of the spheroidized carbon-based material is: D10 particle size is 3.5 to 7 microns, D50 particle size is 7.5 to 12 microns, and D90 particle size is 16 to 30 microns; and / or The tap density of the spheroidized carbon-based material is ≥0.7 g·cm 3 .

7. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In the step S12, the spheroidizing and shaping machine used in the spheroidizing and shaping process is selected from an impact spheroidizing and shaping mill, a batch shaping machine, an air flow vortex mill or an air flow classifier.

8. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In the step S13, the particle size distribution of the spherical carbon-based material is as follows: D10 particle size is 3 to 7 microns, D50 particle size is 7 to 12 microns, and D90 particle size is 15 to 30 microns.

9. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 2, characterized in that: In step S13, the fusion shaping process uses a fusion machine.

10. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 1, characterized in that: In the step S1, the carbon-based material is one or more of natural graphite, artificial graphite precursor, artificial graphite and negative electrode dust removal powder.

11. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 1, characterized in that: The specific process of step S2 is as follows: A wet grinder is used for wet grinding, and zirconium beads with a diameter of 0.4 to 3 mm are used as wet grinding media. The spherical carbon-based material, solvent and dispersant are added into the barrel of the wet grinder, and low-speed pre-stirring is first performed to fully mix the spherical carbon-based material, solvent and dispersant. The grinder is then operated at a speed of 1000 to 4000 r / min, and samples are taken every 2 hours for particle size testing. After the particle size meets the requirements, the zirconium beads are separated to obtain a carbon-based material dispersion with a D50 particle size of 0.5 to 3 microns.

12. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 11, characterized in that: In the step S2, the stirring rate of the low-speed pre-stirring is 300-600 r / min.

13. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 11, characterized in that: In the step S2, the particle size detection adopts laser particle size test.

14. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to claim 1, characterized in that: In step S2: The solid-to-liquid ratio of the mixture of the spherical carbon-based material, the solvent and the dispersant is 1:2 to 1:4; and / or The proportion of the dispersant in the mixture of the spherical carbon-based material, the solvent and the dispersant is 1 to 10 wt‰; and / or The solvent is deionized water; and / or The dispersant is selected from one or two of KYC-913, KYC-9366 of Keying Chemical, and BYK-P104 of BYK Chemical.

15. The method for preparing a carbon-based material dispersion for a high temperature molten salt corrosion resistant coating according to any one of claims 1 to 14, characterized in that: The particle size distribution of the carbon-based material dispersion is as follows: D10 particle size is 0.1 to 1.5 microns, D50 particle size is 0.5 to 3 microns, and D90 particle size is 1.5 to 6.5 microns.

Citation Information

Patent Citations

  • Chloride molten salt corrosion resistant coating and preparation method thereof

    CN115418592A